Beispiel Nr: 15
$ \text{Gegeben:} ax^{3}+bx^{2}+cx+d=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ \\ \textbf{Gegeben:} \\ -\frac{1}{2}x^3-\frac{1}{2}x^2+4x+6 =0\\ \\ \textbf{Rechnung:} \\\\-\frac{1}{2}x^3-\frac{1}{2}x^2+4x+6=0 \\\\ \text{Nullstelle für Polynmomdivision erraten:}-2\\ \,\small \begin{matrix} (-\frac{1}{2}x^3&-\frac{1}{2}x^2&+4x&+6&):( x +2 )=-\frac{1}{2}x^2 +\frac{1}{2}x +3 \\ \,-(-\frac{1}{2}x^3&-1x^2) \\ \hline & \frac{1}{2}x^2&+4x&+6&\\ &-( \frac{1}{2}x^2&+x) \\ \hline && 3x&+6&\\ &&-( 3x&+6) \\ \hline &&&0\\ \end{matrix} \\ \normalsize \\ \\ -\frac{1}{2}x^{2}+\frac{1}{2}x+3 =0 \\ x_{1/2}=\displaystyle\frac{-\frac{1}{2} \pm\sqrt{\left(\frac{1}{2}\right)^{2}-4\cdot \left(-\frac{1}{2}\right) \cdot 3}}{2\cdot\left(-\frac{1}{2}\right)} \\ x_{1/2}=\displaystyle \frac{-\frac{1}{2} \pm\sqrt{6\frac{1}{4}}}{-1} \\ x_{1/2}=\displaystyle \frac{-\frac{1}{2} \pm2\frac{1}{2}}{-1} \\ x_{1}=\displaystyle \frac{-\frac{1}{2} +2\frac{1}{2}}{-1} \qquad x_{2}=\displaystyle \frac{-\frac{1}{2} -2\frac{1}{2}}{-1} \\ x_{1}=-2 \qquad x_{2}=3 \\ \underline{x_1=-2; \quad2\text{-fache Nullstelle}} \\\underline{x_2=3; \quad1\text{-fache Nullstelle}} \\$